1982
DOI: 10.1017/s0033291700049175
|View full text |Cite
|
Sign up to set email alerts
|

The Disability Assessment Schedule: a brief screening device for use with the mentally retarded

Abstract: SynopsisVarious types of reliability measures were conducted on the Disability Assessment Schedule, a structured interview devised to elicit from parents or care staff details of impairments, skills and behaviour problems in mentally retarded children and adults. The results indicated high overall agreement when the schedule was repeated over time, and also when used by several trained interviewers to rate the same interview. Problems arising from the use of such interview schedules are discussed, and suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
161
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(169 citation statements)
references
References 4 publications
0
161
0
8
Order By: Relevance
“…Quality of social interaction and symbolic activities are assessed under abnormalities of social and imaginative activities, which is reported by the authors to have satisfactory reliability (test-retest 82%, inter-respondent: 68% and inter-rater: 75-79%; Holmes et al 1982). Similarly, the reliability of the stereotypy section is reported to be 77% for test-retest, 85% for interrespondent agreement and 80-82% for inter-rater agreement.…”
Section: Presence Of Autism Spectrum Disordermentioning
confidence: 88%
See 1 more Smart Citation
“…Quality of social interaction and symbolic activities are assessed under abnormalities of social and imaginative activities, which is reported by the authors to have satisfactory reliability (test-retest 82%, inter-respondent: 68% and inter-rater: 75-79%; Holmes et al 1982). Similarly, the reliability of the stereotypy section is reported to be 77% for test-retest, 85% for interrespondent agreement and 80-82% for inter-rater agreement.…”
Section: Presence Of Autism Spectrum Disordermentioning
confidence: 88%
“…The presence of ASD was determined by meeting threshold levels on three sections of the Disability Assessment Schedule (DAS; Holmes et al 1982): quality of social interaction, stereotyped behaviors, and symbolic activity The DAS was designed to be used as a screening instrument of the abilities, disabilities and problem behaviors of individuals with ID. Quality of social interaction and symbolic activities are assessed under abnormalities of social and imaginative activities, which is reported by the authors to have satisfactory reliability (test-retest 82%, inter-respondent: 68% and inter-rater: 75-79%; Holmes et al 1982).…”
Section: Presence Of Autism Spectrum Disordermentioning
confidence: 99%
“…However, those authors did not use actual measures of autism or autistic behavior. Instead the Disability Assessment Schedule [DAS; Holmes et al, 1982] and items from the MRC Schedule of Handicaps, Behaviours and Skills [HBS; Wing, 1980] were used to assess changes in autistic behaviors over a 10-year period in 18 adults with FXS whose mean age was 46.1 years at the time of follow-up. They found that ratings of autistic behaviors were stable over time in this group.…”
Section: Stability Of Autistic Behavior In Fxsmentioning
confidence: 99%
“…ABS-Aberrant Behaviour Schedule-Community (Aman, Burrow, & Wolford, 1995) PAS-ADD checklist (Moss, Prosser, Costello, Simpson, Patel, Rowe, Turner, & Hatton, 1998) DAS-Disability assessment Schedule (Holmes, Shah, & Wing, 1982) …”
mentioning
confidence: 99%